National Curriculum Development: Should Teachers be Engaged in Developing it? - Ricky Fernandes (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
The success of designing and implementing national curriculum development could significantly depend on teachers, as they inform ideas and practices into real classroom settings. Engaging teachers in the early stages of designing the curriculum can also enhance their perspectives and understanding of knowledge reformation. From this notion, the conception of teachers as curriculum developers and practitioners could be an alternative movement to improve better education quality. However, little is known about offering to establish teachers’ expertise and knowledge in designing and developing national curriculum. This is in part because the approach, which is a top-down approach, in some educational settings does not utilise teachers’ perceptions, understanding and experiences to design national curriculum. Moreover, to engage teachers’ voices in national curriculum development, knowledge to expand and transform subject matters into the provision of better student outcomes are required. Although the enactment for teachers to promote national curriculum development is still being examined, teachers' roles, in the contexts of educational policies and practices, should be considered to reform better student outcomes. Therefore, this literature review will discuss teachers’ roles and engagement in national curriculum development.